Minimally invasive liver resections: a changing landscape and the rise of the robot - Beard, Rachel E.; Tsung, Allan (Laparoscopic Surgery, 2018)
Minimally invasive techniques are increasingly employed for liver resections for both oncologic and non-oncologic indications, and the safety and non-inferiority of both laparoscopic and robotic-assisted techniques as compared to the gold standard of open surgery is increasingly well-established (1-9).